Chemical Changes of Cassava During Processing of Growol which Made from Different Cassava Variety and Cooking Method: Perubahan Sifat Kimia Ubikayu Selama Pengolahan Growol yang Dibuat dengan Variasi Varietas Ubikayu dan Cara Penanakan - Wariyah, Chatarina; Slamet, Agus; Riyanto, Riyanto (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2024)
Growol is a traditional food made from cassava and processed through soaking/spontaneous fermentation. Growol has the potential as a prebiotic because of its resistant starch content. Currently, growol processing uses the local cassava variety of Martapura. It is cooked by steaming, whereas there are many cassava varieties, and the cooking method also affects the growol characteristics. This study aimed to evaluate the chemical changes of cassava with different varieties and cooking methods during growol processing to obtain growol with the potential as a prebiotic. This research was conducted in a completely randomized design with two factors, namely cassava varieties ("Ketan", "Lanting," and "Mentega") and cooking methods with a variation of: steaming, autoclaving, and pressure cooker. The samples were analyzed for their moisture, starch, and amylose content at each processing stage. Growol with high amylose content was evaluated for its prebiotic index using probiotic bacteria Lactobacillus rhamnosus. The results showed that processing growol with an autoclave of Lanting variety produced a high amylose content of 11.65 ± 2.33% with a prebiotic index of 0.16 ± 0.02.